Fards al-Jinn: A compact Acehnese translation for learning Jurjn's rudimentary Arabic grammar in Aceh - Rizki, Syukri; Yusrizal, Yusrizal (Universitas Syiah Kuala, 2025)
Arabic, regarded as the language of the educated in both present and past Aceh, facilitates the comprehension of numerous Islamic didactic texts authored by scholars from the Arab world and other Muslim regions. A widely studied text connecting the Acehnese people to this scholarship is Jurjns manual, designed to introduce basic grammatical rules to Arabic beginners. Toward the end of the twentieth century, the prolific Acehnese scholar Abu Teupin Raya (Teungku Muammad Al Irsyd) translated Jurjns text into the Acehnese language under the title Fards al-Jinn f Tarjamah al-Awmil al-Jurjn bi Lisn al-Ulam al-Qudam bil-sy, aiming to simplify Arabic grammar for Acehnese students. This paper explored into the oral features of the text, examining the constants and patterns in the relationship of Arabic, Malay, and Acehnese languages. It highlighted the authors method of using Acehnese language to render the original Arabic source and discussed the exclusivity of Acehnese as an official language within the dayah (traditional Islamic schools). Using the Faircloughian Critical Discourse Analysis (CDA) approach, the text was analyzed as discourse fundamentally linked to its socio-political context. The study employed a three-layer interpretation (micro, meso, and macro levels), as suggested by the approach. The findings revealed that the literal translation technique employed by Abu Teupin Raya reflects an oral translation mode commonly practiced by teachers in Acehnese traditional Islamic schools. Furthermore, the awareness of Aceh as a distinct nation was already evident during the authors lifetime, highlighting the linguistic distance between Acehnese and other languages, especially Arabic and Malay.